2019
DOI: 10.1002/lsm.23144
|View full text |Cite
|
Sign up to set email alerts
|

Laser Ablation of Benign Thyroid Nodules: A Prospective Pilot Study With a Preliminary Analysis of the Employed Energy

Abstract: Background and Objectives To assess the effectiveness of ultrasound (US)‐guided laser ablation of benign thyroid nodules (TNs) under different amounts of applied energy. Study Design/Materials and Methods Thirty‐four euthyroid patients with 5–18 ml TNs were enrolled: 21 (laser ablation) and 13 (clinical follow up) patients with a mean age of 56.2 ± 12.0 and 54.7 ± 14.7 years, respectively. The laser ablation protocol used a 1.064 mm wavelength diode laser source; 3.5 W output power; 1,100–1,500 J and 5–8 min/i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
1
14
1
Order By: Relevance
“…A recent study showed that when using laser ablation, higher energy deployment may be associated with improved results; between two groups of nodules undergoing different energy treatments, the one treated with a mean of 599.9 ± 136.5 J/ mL obtained a VRR greater than the one treated with a mean of 240.2 ± 74.6 J/mL. The authors calculated that > 398.8 J/ mL should be used to obtain better results (26). Though one might hypothesize that the regrowth rate we observed was influenced by the relatively low amount of energy supplied, the results undoubtedly showed that similar amounts of energy exerted different results in terms of VRR.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that when using laser ablation, higher energy deployment may be associated with improved results; between two groups of nodules undergoing different energy treatments, the one treated with a mean of 599.9 ± 136.5 J/ mL obtained a VRR greater than the one treated with a mean of 240.2 ± 74.6 J/mL. The authors calculated that > 398.8 J/ mL should be used to obtain better results (26). Though one might hypothesize that the regrowth rate we observed was influenced by the relatively low amount of energy supplied, the results undoubtedly showed that similar amounts of energy exerted different results in terms of VRR.…”
Section: Discussionmentioning
confidence: 99%
“…For benign cold thyroid nodules, clinical follow‐up and several ablative methods, including LA, RFA, MWA, and HIFU, have been applied to these nodules and these ablative methods have demonstrated good results, and LA appears to be superior to the other methods, due to its advantages. A prospective pilot study demonstrated that LA group achieved technique efficacy and clinical improvement in contrast to clinical follow‐up group . A 3‐year, multicenter, prospective randomized trial demonstrated that LA obtained long‐term efficacy, with an absence of thyroid function changes .…”
Section: Discussionmentioning
confidence: 98%
“…As different tissues have different characteristics, such as the amount of colloid, both fibrosis and vascularity may possibly account for the different optical properties of the nodule, thereby resulting in differences in responsiveness and a demand for the amount of deposited energy . In this study, a 5‐ml‐volume upper limit existed for the benign cold thyroid nodules, which is only a preliminary inclusion that was dependent on our experiences and previous studies . However, the feasibility and effectiveness of ultrasound‐guided single‐fiber LA were evaluated, and the appropriate ablation modes for these selected nodules were performed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations